SOCIO-ECONOMIC CONSEQUENCES OF IMMIGRATION IN ITALY - Elena J. Tsareva (Vestnik MGIMO-Universiteta, 2014)
During the last decade, migration flows have greatly affected the Italian economy and demography. The trend is growing, not only because of the ideal geographic position for transit, but also due to the Italian economic structure, and business interest: Cheap labour is greatly in demand among employers. The increasing number of migrants has created a certain imbalance in different spheres of life and society. The middle-aged population in Italy is ever growing, thus migrants play an important role in filling the workforce depletion as well as flooding the labor market. The effects of migration cannot be viewed as either positive or negative. In the recent decade, Italy has been pursuing a tight budgetary policy regarding its obligations under the Economic and Monetary Union. At the same time, the government realizes the necessity of radical restructuring of the national market, both taking measures to encourage entry of fully qualified migrants and by restricting illigal or low-skilled immigrants. The state faces a number of problems, such as job placement and assimilation of migrants into society. Some of the objectives are to provide them with the employment, cultivate European values and teach them Italian. While migrants are relevant, the shadow sector of the economy - sheltering iltygals - is growing. The economy and the budget suffer, and the external debt is growing. The article presents the data on the demographic situation in Italy. It analyzes the correlation between the migrants and the indigenous people in the labor market. Special attention is focused on socioeconomic consequences of immigration in Italy. International experience in general and Italian in particular are highly important to improving the migration policy, developing systems of internal and external control of the migration processes, illegal migration control, and a quota system; the government even takes note of fertility among migrants. A comprehensive analysis of these trends seems promising toward improving the Italian migration policy.